Peningkatan kompetensi guru melalui pemanfaatan teknologi informasi dan komunikasi bagi Guru SMP di Kabupaten Bulukumba - Sulaiman Sulaiman; Maya Maya; Rahmat Rahmat (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Regulation of the Minister of Education and Cultural Number 69 Year 2013 concerning the basic framework and structure curriculum of Junior High Schools which is no longer includes Information and Communication Technology (ICT) as subjects in both primary and secondary education but ICT is integrated in all subjects. This means that even though ICT is not included as subjects, this skill is absolutely necessary in the learning process. The application of ICT in education is the use of multimedia facilities in the learning process. The use of multimedia as a learning tool can be done in the form of a more interactive learning modules so that it can attract the interest of students. The use of ICT in SMPN 30 Bulukumba in teaching and learning process is not optimal yet. It is because the facilities are not optimal and there are still many teachers who have not mastered ICT. Learning innovation by utilizing ICTs needs to be done in order to make the students interested to study. Teachers need to have in utilizing and implementing ICT in the teaching and learning process in the classroom in the form of quality improvement in the classroom. Teachers and students must have access to ICT in the school environment. Therefore, teachers must have the knowledge and skills in using ICT so they can help their students in achieving academic standards and develop their potentials. Accordingly, ICT training needs to be carried out according to the needs of the school.